Enforcement of the EU ETS : the EU's convulsive efforts to export its environmental values - Mendes de Leon, Pablo (2012)
Posits that the legal foundations of the EU ETS 2008/101 directive, establishing a scheme for greenhouse gas emission allowances trading within the Community, does not take into account mandatory international law provisions, or even manipulates international law for the purpose of achieving the environmental goals envisaged by the drafters. Argues that international law considerations must be taken into account when fostering environmental policies which affect international trade or the operation of international air services.